Hybrid Mismatches After the ATAD in the Czech Republic - Lukáš, Hrdlička (Wolters Kluwer, 2022)
Kniha se věnuje problematice hybridních nesouladů a argumentuje ve prospěch jejich řešení jiným způsobem, než které zvolily OECD a EU. Za tímto účelem kniha seznamuje čtenáře s pojmem hybridní nesoulady a jejich příklady i důsledky. Dále se věnuje řešení hybridních nesouladů, které zvolilo OECD a následně převzala EU ve směrnici, kterou se stanoví pravidla proti praktikám vyhýbání se daňovým povinnostem, které mají přímý vliv na fungování vnitřního trhu (směrnice ATAD 1) a její novelizaci (směrnice ATAD 2). Kniha se krátce zabývá také českou transpozicí této směrnice a možnostmi států používat alternativní řešení hybridních nesouladů, i když už EU zvolila řešení ve směrnici prostřednictvím tzv. linking rules, které místo hybridních nesouladů samotných řeší pouze jejich daňové důsledky. The book explores the issue of hybrid mismatches and argues in favor of addressing them in a different way than the OECD and the EU have chosen. To this end, the book introduces the reader to the concept of hybrid mismatches, their examples, and their implications. The book then examines the solutions to hybrid mismatches chosen by the OECD and subsequently adopted by the EU in the Directive laying down rules against tax avoidance practices directly affecting the functioning of the internal market (ATAD 1) and its amendment (ATAD 2). The book also briefly discusses the Czech transposition of the Directive and the possibilities for states to use alternative solutions to hybrid mismatches, even though the EU has already chosen to address the Directive through the so-called linking rules, which instead of addressing hybrid mismatches themselves only address their tax consequences.
Keywords: Daně